2007
DOI: 10.1051/0004-6361:20065400
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative comparison between type Ia supernova spectra at low and high redshifts: a case study

Abstract: We develop a method to measure the strength of the absorption features in type Ia supernova (SN Ia) spectra and use it to make a quantitative comparisons between the spectra of type Ia supernovae at low and high redshifts. In this case study, we apply the method to 12 high-redshift (0.212 ≤ z ≤ 0.912) SNe Ia observed by the Supernova Cosmology Project. Through measurements of the strengths of these features and of the blueshift of the absorption minimum in Ca ii H&K, we show that the spectra of the high-redshi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 56 publications
4
52
2
Order By: Relevance
“…3 (left panel), measurements are made of their pseudo-equivalent width (pEW), which is a common method to quantify spectral properties of SNe Ia at optical wavelengths (e.g., Folatelli 2004;Garavini et al 2007;Folatelli et al 2013). Parameters that define the two UV pEW indicators considered here were obtained following the prescription of Garavini et al (2007) and are summarised in Table 9. In short, the two pEW indicators are defined from the blue to the red maximum of an absorption trough.…”
Section: Uv Pseudo-equivalent Widthmentioning
confidence: 99%
“…3 (left panel), measurements are made of their pseudo-equivalent width (pEW), which is a common method to quantify spectral properties of SNe Ia at optical wavelengths (e.g., Folatelli 2004;Garavini et al 2007;Folatelli et al 2013). Parameters that define the two UV pEW indicators considered here were obtained following the prescription of Garavini et al (2007) and are summarised in Table 9. In short, the two pEW indicators are defined from the blue to the red maximum of an absorption trough.…”
Section: Uv Pseudo-equivalent Widthmentioning
confidence: 99%
“…Although the minima of the spectral features is not going to be strongly affected (thus the v), both the slope of the pseudo-continuum and its deepness would be affected. Nordin et al (2011) and Garavini et al (2007) studied the effect of reddening in the uncertainties of pW measurement and concluded that for values of E(B − V ) lower than 0.3 the difference is lower than 5%, but for more extinguished SN it could be important, which is the case of SN 2014J. Observed unredshifted pre-maximum, maximum-light, and post-maximum spectra taken at ORM (La Palma).…”
Section: Measurement Of the Spectral Parametersmentioning
confidence: 99%
“…Observational trends appear to emerge in the way the velocities within the supernova ejecta evolve , but the interpretation of these correlations are not clear yet. It is noteworthy that the distant objects appear to follow the general spectral evolution of their nearby counterparts and there is no obvious sign of differences in the spectral appearance of SNe Ia (Blondin et al 2006, Garavini et al 2007b. The interpretation of the spectra has now also been expanded to reconstruct the element distribution in the ejecta through the spectral evolution (Fisher et al 1999, Stehle et al 2005, which gives a direct input to the explosion models.…”
Section: Type Ia Supernovaementioning
confidence: 99%